Kidney transplant-related knowledge and influencing factors in Chinese kidney transplant candidates and recipients: A cross-sectional study - Ma, Hangxia; Hu, Maosen; Wan, Jingjing (Frontiers in Public Health, 2023)
Objective: To investigate the knowledge level of kidney transplant (KT) candidates and recipients, and to explore the related influencing factors. Methods: From March to July 2022, a total of 170 KT candidates and 270 KT recipients were investigated in two tertiary and Grade A hospitals in Hunan Province, China, using demographic questionnaires and the Kidney Transplant Understanding Tool (K-TUT). Multiple linear regression was used to explore the influencing factors of related knowledge of kidney transplantation. Results: The scores of kidney transplantation knowledge of the two groups were 50.67 and 52.79, respectively, which were in the middle level. Education level and whether they have received health education are the influencing factors of both. But age and fertility status were the influencing factors of KT recipients. Conclusion: Healthcare providers should pay attention to the above factors, which can help to identify the weak points of KT knowledge of KT candidates and recipients, and provide reference for formulating targeted health education and improving their knowledge level.